Achondroplasia: Craniofacial manifestations and considerations in dental management - Afnan Al-Saleem; Asma Al-Jobair (Saudi Dental Journal)
Achondroplasia is the most common form of skeletal dysplasia dwarfism that manifests with stunted stature and disproportionate limb shortening. Achondroplasia is of dental interest because of its characteristic craniofacial features which include relative macrocephaly, depressed nasal bridge and maxillary hypoplasia. Presence of large head, implanted shunt, airway obstruction and difficulty in head control require special precautions during dental management. Craniofacial manifestations and considerations in dental management are presented in 11-year-old female patient with achondroplasia. Keyword: Achondroplasia